Reviewing the Prosperity Tracks After Two Decades of Special Autonomy for Papua - Hendy Setiawan (Soshum: Jurnal Sosial dan Humaniora, 2022)
The purpose of this study is to discuss the impact of the implementation of special autonomy which has been running for two decades on welfare in Papua through the public service sector. Law Number 21 of 2001 which became the initial basis for the implementation of special autonomy in Papua is an instrument to encourage Papua to catch up with other regions in Indonesia. So far, Papua has been an area that tends to be left behind in various sectors, including its public services. Therefore, the presence of special autonomy, which is then followed by special autonomy funding that significantly increases every year, is expected to be able to improve public services to achieve prosperity. This study uses a qualitative method with a literature study approach. Data were collected from various literature, both from relevant agencies and the relevant media. Meanwhile, researchers in conducting research stages use the Creswell concept. The stages of this research consist of problem identification, literature search, research aims and objectives, data collection, data analysis and interpretation, and research reporting. The results of the study show that two decades of implementing special autonomy in Papua have not provided significant achievements for public services. High poverty rates, low Human Development Index and minimal public service facilities are still the main characteristics of the implementation after the two decades of autonomy. The implication is that there is a negative correlation between the implementation of this special autonomy and the welfare aspect to date. Therefore, the disbursement of funds that enter from the centre to the regions through this regulatory scheme has not had a significant impact on welfare in Papua.